Educational priorities for primary care providers on systemic lupus erythematosus in the Caribbean - Lawrence, Jannel; King, Amanda; Ramessar, Nina; Henry, Danielle; Davis, Stacy; Davis-King, Keisha; McGhie, Taniesha; Rolle, Anishka; Manno, Rebecca; Dowell, Sharon (Frontiers in Lupus, 2024)
Introduction: Systemic lupus erythematosus (SLE) is highly prevalent in the Caribbean, with limited access to specialist care. Primary care providers (PCPs) must play a key role in SLE management but lack specific knowledge on high-impact diagnostic and management strategies for the Caribbean SLE patient. The Caribbean Association for Rheumatology (CAR) supports PCPs with educational material tailored to the Caribbean but is limited by poor regional data on SLE educational needs. The aim of this project was to achieve consensus amongst CAR members on SLE educational priorities for PCPs based on individual experience.The nominal group technique was used to achieve consensus. Participants were asked to generate, record, discuss and rank ideas, which were organized by emergent categories. Each participant assigned a score to their top ideas, generating a group-level score for each topic. A threshold of at least 70% agreement was set for consensus. Narrative comments from the discussion and ranking survey provided context for the consensus topics.Results: 13 providers (9 rheumatologists and 4 internists), mostly female (92%), mean age 42.4 (8.2) years, participated. There was consensus on 15 topics which emphasized early diagnosis, early rheumatology referral and reproductive health. Of the top-ranked topics, there was a trend towards a primary care focus amongst internists.